Just Sinus Bradycardia or Something More Serious?. (11th February 2013) - Egan, Kelly R.; Ralphe, J. Carter; Weinhaus, Larry; Maginot, Kathleen R.
Abstract : An asymptomatic 5-year-old girl presented with bradycardia during a routine well-child visit. Further evaluation revealed profound sinus bradycardia, exercise-induced bidirectional ventricular tachycardia, and supraventricular tachycardia. An echocardiogram showed heavy trabeculations in the left ventricular myocardium. This patient's presentation suggested catecholaminergic polymorphic ventricular tachycardia and left ventricular noncompaction. Genetic testing revealed mutations in the cardiac ryanodine receptor (RyR2), calsequestron (CASQ2), and titin (TTN). She was effectively treated with beta-blockade to suppress tachyarrhythmias and pacemaker implantation to treat her bradycardia.